KEWENANGAN, KEKUASAAN, DAN PENGARUH KEPEMIMPINAN PENDIDIKAN (Berlandaskan Tinjauan Agama, Filsafat, Psikologi dan Sosiologi di SDN 198 Mekarjaya) - Yanti Krismayanti; Irma Anggraeni; Jajang Supriatna; Ishak Abdulhak; Achmad Mudrikah (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2021)
The decision-making taken by the school leadership must be participatory, meaning that all components of the school community must be involved in the decision-making process carried out by the leader, but if you look at the various phenomena that appear in the field, it turns out that there are still many principals in making decisions centrally. With the existence of centralized decision-making, the execution of the results of the decision could not go well because the school community felt that they were not involved in the decision-making. To obtain good decision results and can be implemented by those with good interests, of course, there needs to be a more in-depth study of how to make participatory decisions by exploring knowledge about authority, power, and leadership influence. The three scientific study activities focused on the basic education level by taking a case study at SDN 198 Mekarjaya, Bandung. From the scientific study of the three components, several research problems were formulated to seek answers about the relationship between authority, power, and leadership influence. Education-based on religious, philosophical, psychological, and sociological reviews. The research method uses a qualitative approach to the type of case study in one of the basic education institutions at SDN 198 Mekarjaya, Bandung City. The results of the research on the authority, power, and influence of leadership at SDN 198 Mekarjaya based on a religious review show that the education leadership, in this case, the principal, always acts on a religious basis. Judging from the philosophical basis that the principle always applies the values ​​of ethical idealism in each of his main tasks. Judging from the psychological basis, the principal in making decisions or policies is very careful and always considers input from various parties. Judging from the social basis, the principal in carrying out school management is quite mastered. Recommendations from the results of the study, that the principal of both kindergarten, elementary, high school / vocational school, is better in carrying out educational leadership in schools always positioning himself as a democratic leader and manager, prioritizing deliberation, and being able to make participatory decisions so that school residents feel involved directly so that an attitude arises to carry out the decision voluntarily. Forced decisions are usually not good. Principals in using authority, power, and influence in schools should apply wisely so that educational goals can be achieved properly without any negative excesses.